Evaluation on fatigue behaviour of spot-welded joint under low blow impact treatment (Fracture and Structural Integrity, 2022)
Welding is used widely in modern industries to combine parts needed complete a product. In this paper, we investigated the effect of post-weld impact treatment (PWIT) on spot-weld joints and evaluate the tensile and fatigue properties of the specimens. Currently, there is no simple failure criterion capable of predicting the strength of a spot weld under different loading conditions. The reliability of spot-welded structures treated with PWIT in terms of fatigue integrity could be understood more by the end of this research. The result showed that not only the tensile properties of PWIT specimens give an improvement, but there was also a significant increase in the fatigue life of the treated specimens.
Keywords: Fatigue; Post-weld; Welding; PWIT